PEDIOCOCCUS PENTOSACEUS CECT 8330 AND BIFIDOBACTERIUM LONGUM CECT 7894 SHOW A TREND TOWARDS LOWERING INFANTILE EXCESSIVE CRYING SYNDROME IN A PILOT CLINICAL TRIAL - JONATHAN SANTAS,; MARI CARMEN FUENTES,; RAMON TORMO,; RAFAEL GUAYTA-ESCOLIES,; ELISABET LÁZARO,; JORDI CUÑÉ, (International Journal of Pharma and Bio Sciences, 2015)
The aim of this study was to evaluate the in vitro probiotic properties of Pediococcus pentosaceus CECT 8330 and Bifidobacterium longum CECT 7894 and their suitability as candidates for treating infantile excessive crying syndrome. Results reveal that P. pentosaceus is able to induce IL-10 production, and the combination with B. longum CECT 7894 shows a broad spectrum inhibitory activity against pathogens. P. pentosaceus CECT 8330 and B. longum CECT 7894 were combined in a single formula which was confirmed to be well tolerated in a pilot, randomized, double-blind clinical trial in infants with excessive crying syndrome. Moreover, a trend towards a greater reduction in daily crying time was observed in the probiotic group compared to placebo (81.0 ± 11.2 vs 54.1 ± 8.6 reduction in minutes per day, respectively; P=0.083). Given the small sample size, these analyses should be repeated in a larger study.